OVERVIEW ON AN OPEN PIT MINE PLANNING OF THE PICKSTONE PEERLESS IN A VOLATILE ENVIRONMENT - Tapiwa Frank Kwachara Ngoroyemoto; Charles Chewu; Desire Runganga; Tatenda Nyamagudza; Ashley Ruvimbo Sabao (Puslitbang tekMIRA, 2022)
The prevailing mining climate is highly characterized by unstable consumables pricing systems, a volatile economy and skyrocketing operational costs, and exacerbated by a steady decline and intermittence in the availability of electricity. Zimbabwean mines need to extensively capitalize on the opportunity to improve productivity by emphasizing variables they can control, predominantly operational efficiency to avoid resizing of operations or facilitating downsizing by relatively insignificant factors. In this study, cycle times, rig penetration, utilization, availability and payloads were used to evaluate the mining cycles, operator costs and the information was compared against the life of mine plans with block models. Shifts were restructured to be concordant to the schedule provided by the utility company to save fuel that was being used to power metallurgical plant. Several challenges have been identified as the principal reasons behind discrepancies between the theoretical capabilities of equipment were proven to be achievable by a trial schedule which reduced the 7 days/month to less than 2 days a month. The new schedule reflects a theoretical improvement of close to 25% and significantly lower operational costs. The current mining fleet is capable of meeting the stipulated targets and even achieving more even within tough working environments characterized by harsh load shedding schedules and volatile inflation rates; however, this requires stringent monitoring and evaluation of unit process. By adopting the recommended short term production plans will avoid resizing of operations as it automatically reduces the operational costs by US 3 million annually whilst coercing both operators and management to improve their operational efficiency.